2012
DOI: 10.1089/scd.2012.0095
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Stimulated by Hypoxia Promote Angiogenesis Both In Vitro and In Vivo

Abstract: Although mesenchymal stem cells (MSCs) have been increasingly trialed to treat a variety of diseases, the underlying mechanisms remain still elusive. In this study, human umbilical cord (UC)-derived MSCs were stimulated by hypoxia, and the membrane microvesicles (MVs) in the supernatants were collected by ultracentrifugation, observed under an electron microscope, and the origin was identified with the flow cytometric technique. The results showed that upon hypoxic stimulus, MSCs released a large quantity of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
3
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(209 citation statements)
references
References 60 publications
4
199
3
3
Order By: Relevance
“…Accumulating evidence has indicated that MVs could modulate various processes, such as vascular function, angiogenesis, cell proliferation, inflammation, and coagulation [10,23,24] . Cord blood-derived MSC-MVs may promote angiogenesis in vitro and in vivo [25] . A recent study showed that the administration of MSC-exosomes can promote functional recovery and neurovascular plasticity in a stroke model [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that MVs could modulate various processes, such as vascular function, angiogenesis, cell proliferation, inflammation, and coagulation [10,23,24] . Cord blood-derived MSC-MVs may promote angiogenesis in vitro and in vivo [25] . A recent study showed that the administration of MSC-exosomes can promote functional recovery and neurovascular plasticity in a stroke model [10] .…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are stromal cells with multipotent differentiation capacity and have been intensively investigated for their potential regenerative and immunosuppressive effects in many animal models and clinical trials. Although originally believed to be the result of MSC homing to and engraftment at injured tissues, it is now becoming increasingly clear that the biological effect of these cells is mainly attributed to their secretome, including EVs [93,94]. In this respect, MSCderived EVs have been studied in dedicated mouse models for their tissue-protective effects following acute kidney failure [93], myocardial infarct [95], liver injury [96] and neural injury after middle cerebrate artery occlusion [97].…”
Section: Harnessing the Intrinsic Biological Effect Of Evsmentioning
confidence: 99%
“…Several studies demonstrate that small cellularly secreted vesicles called exosomes mediate much of MSCs' tissue healing capabilities [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. MSC derived exosomes are internalized by target cells and transfer proteins, RNA, lipids and metabolites [29].…”
Section: Phenotype Of Mscsmentioning
confidence: 99%